Phytochemical evaluation and exploration of the hepatoprotective activity of 5 different formulations in CCL4 induced albino RATS - Patel, Hardik; Patel, Nilesh; Patel, Janmejay; Patel, Payal; Patel, Apurva (International Journal of Pharmacology and Toxicology, 2016)
Background: Hepatotoxicity and Liver disorders are chronic disorders due to different causes. It affects people in their prime of life, predominantly between the ages of 25-75 years with unpredictable courses. The different formulations are assumed to have significant activity in the treatment of the Liver disorders.Objective: The present study planned to evaluate the synergistic efficacy activity of the different formulations using CCL4 induced hepatotoxic model albino rats.Materials & Methods: The Phytochemical analysis of the T.cordifolia and five different formulations were performed. The animals were divided into eight different groups of 6 animals each as CCl4 treated, Single Plant extracts treated and another different test drug treated groups except 1st group, which was treated with only normal saline. The drugs were administered orally, twice a day and continued for 20 days. On the last day, all the group of animals were treated with the 1ml/kg CCl4 I.P. The Statistical significance was assessed using One-way ANOVA.Results: It was observed that 5 different formulations, i.e. Herbolive Syrup, Hepatonej Syrup, Hepanej Capsule, Herbolive Capsule, and Hepatonej Capsule produced significant hepatoprotective effect on 21st day. All the Formulations have significantly reduced the elevated level of Total Bilirubin, Direct Bilirubin, SGPT, SGOT, and ALP level.Conclusion: The result reveals that all the Herbomineral formulations possess the better hepatoprotective activity compare to single T.cordifolia plant extract. It is due to synergistic action of the various plants and minerals used into the formulation which brings down the elevated liver damage parameter to almost normal level.